PEMBENTUKAN AKHLAQUL KARIMAH BERBASIS PEMADUAN SEKOLAH DAN PESANTREN - Asrori, Achmad (Universitas Islam Negeri Raden Intan Lampung, 2014)
This paper attempts to formulate good moral formation through the integration pattern of superior value of Ordinary School and Boarding School. This attempt is particularly relevant to the current situation where the Indonesian nation is facing serious challenges, especially in the context of good moral community development. The strategy offered rests on the development of psycho-Sufi (Sufism) which is integrated in the two forms of activities, namely: (a) the day-to-day activities- by examples, spontaneous activities, reprimands, environmental conditioning, and routine activities; and (b) programed activities- by the preparation of lesson plan loaded with good moral values. The steps to be taken such as: (1) identification of basic competencies of a subjects including its measurement indicators; (2) identification of good moral values, combined with science and technology; (3) selection of appropriate teaching materials; (4) implementation of the learning activities supported by tools / media / sources; (5) evaluation to assess the success of the learning process of science (instructional effect) and good moral values as nurturant effects (side effects) in the learning activities. The Formulation of the interaction models between teachers and students to prepare good moral graduates are conducted through: (a) positioning the interaction between teachers and students within the framework of preparing them to emulate and to follow the footsteps of his teachers. (b) positioning the learner as Talib al-’ilm (the seekers of knowledge) in the school;. and (c) creating an educational interaction atmosphere in the school.